Evaluation of Urban circular economy development: An empirical research of 40 cities in China - Wang, Ning; Lee, Jason Chi Kin; Zhang, Jian; Chen, Haitao; Li, Heng (Journal of cleaner production, 2018)
The city is an important component in the construction of circular economy (CE), and after years of development, assessment of urban CE and calculation of an urban circular development index (UCDI) is an important task that the Chinese government has faced. However, existing research into the indicator system and evaluation methods is not enough to support calculation and subsequent publishing of UCDI. Building off current research into CE, its index systems and its evaluation, this paper puts forward an evaluation index system for urban CE development (UCDI) that uses an improved entropy methodology combining expert and entropy weightings. The index was calculated for 40 cities that were part of China's pilot CE cities program for alternating years in the five year period between 2012 and 2016 (that is, the index was calculated for 2012, 2014 and 2016). The study found that the level of urban CE increased significantly over the five year period, with that in the CE pilot cities growing at a faster rate than the national average. Results show that a certain relationship exists between UCDI, urban types and economic development, but has little relationship with industrial structure. Finally, recommendations for the promotion of urban CE are proposed. •An urban circular development index was developed using Chinese urban statistical data.•The index grew 26.9% from 2012 to 2016 in 40 Chinese circular economy pilot cities.•Annual growth in these pilot cities (5.9%) was higher than the national average (4%).•Residential circularity grew the most; industrial circularity the least.